On the characterisation of uncertainty in performance measurement systems - Sousa, Sérgio (2011)
Performance measurement systems (PMSs) are receiving increasing attention from academics and practitioners particularly after the development of the Balanced Scorecard (BSC), and many PMSs are available nowadays. The hypothesis is that organisations need to reflect the uncertainty of its systems and contextual factors in their PMs to improve their models. This identification of uncertainty in PMS is the first step to reduce such uncertainty. This work provides a classification of uncertainty components that affect the quality of PMs.